ICAME 2007 Proceedings of the 29th International Conference on the Applications of the Ms̲sbauer Effect (ICAME 2007) held in Kanpur, India, 14-19 October 2007 - Gajbhiye, N. S.; Date, S. K. (Springer Berlin Heidelberg, 2009)
Proceedings of the 29th International Conference on the Applications of the Ms̲sbauer Effect (ICAME 2007) held in Indian Institute of Technology, Kanpur, India, 14-19 October 2007 N.S.Gajbhiye and S.K.Date (Eds) This book provides an excellent overview of the Ms̲sbauer Effect in many diverse fields such as Condensed Matter Physics, Solid state Chemistry, Electro and Bio-inorganic Chemistry, Catalyis, Medicine, Geology, Minerology, Archeology and Materials Science, etc. It is of significant interest for graduate students and researchers, who wishes to work in one of the diciplines of Ms̲sbauer Spectroscopy. In addition to the traditional topics, the book contains the recent developments of the technique using Synchrotron Radiation and also in the fields of nanomaterials, surfaces and interfaces, industrial applications and Mars Exploration.